(3eYQGL GdfHj Udi Gddg Ydjg hSde QhGjI GHf YHGSs - (3GdbQTj GdgGTej, GHf YHGS, YHO Gddg Hf YHGS Hf YHO GdeWdH, J(B68(3g`s
(3ChdgG (B:s
(3Qhj Yf GHf YHGS QVj Gddg YfgeG Cfg bGd bGd QShd Gddg Udi Gddg Ydjg hSde HjfeG CfG fGFe Hjf GdUaG hGdeQhI hdSJ HfGFe hcGfJ djdI eeWQI PGJ QYO hHQb hShGO hdG JfHM cdGHgG hdG JUjM OjhcgG EP gHW Ydi GdCejfs
(3BNQgG (B:s
(3hGZaQ dfG hdhGdOjfG hdhGdOj hdeTGjNfG hdef YdefG hdef ajc CMHfG hdef hGdGfG NjQG hdCUMGH GdMbhb YdjfG hdENhGffG GdeSdejf hGdeSdeGJ GdCMjGA efge hGdCehGJ Efc SejY bQjH eLjHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 95s
(3eYLe GdeDdajf(B: 2 / 249s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs